OPTIMIZATION OF IN HOUSE POLYMERASE CHAIN REACTION FOR HIGH RISK HUMAN PAPILLOMAVIRUS (HPV 18) E1 GENE-BASED DETECTION - Naroeni, Aroem; Nirmala Putri Arrasu, Lifda; Saraswati, Henny; Deni Iskandar, Asep (International Journal of Psychosocial Rehabilitation, 2020)
Human Papillomavirus is a virus that can infect human and a causative agent for cervical cancer. This disease mostly caused by HPV type 16 and 18. Polymerase Chain Reaction (PCR) is one of the molecular biology method can be used to detect HPV in sample. Gen E1 in HPV genome has a role in virus replication and transcription, and relatively conserved. This gene can be used in HPV genotyping and detection. This research aim is to find the PCR optimal reaction for HPV type 18 detection. The E1 gene data from the National Center for Biotechnology Information (NCBI) was used in designing primer with Primer-BLAST NCBI. Selection of the primers was done by in silico analyzes using DINAmelt and Mfold. Optimization of annealing temperature and primer concentration was done for selected primers. The result showed that optimal annealing temperature is 59oC with optimal primer concentration is 600 nM